Pickering Emulsion-Based Gels with Halloysite as a Stabilizer: Formulation, Mechanical Properties and In Vitro Drug Release Studies - Anna Froelich (Molecules)
Lidocaine is an analgesic agent frequently incorporated in topical formulations intended for application in minor surgical procedures or relieving neuropathic pain associated with numerous conditions, including post-herpetic neuralgia or diabetic peripheral neuropathy. In this study, Pickering o/w emulsions with halloysite nanotubes as a stabilizing agent and lidocaine incorporated in the internal phase were formulated with the use of the Quality by Design (QbD) approach. The selected emulsions were transformed into semisolid gels with poloxamer 407 as a thickening agent, and investigated for rheological and textural properties, indicating the mechanical features of the obtained gels. Moreover, the obtained formulations were tested for lidocaine release with the use of vertical Franz diffusion cells in order to assess the relationship between the applied composition and potential clinical applicability of the analyzed gels. The obtained results indicate that the emulsion droplet diameter is affected mostly by the oil and halloysite contents. The yield stress points, hardness and cohesiveness values of the obtained gels increased with the oil content. The drug release rate seems to be affected mostly by the concentration of the active ingredient in the oil phase.